RELATIONSHIP BETWEEN BCG VACCINATION HISTORY AND THE INCIDENCE OF LEPROSY IN CHILDREN: A LITERATURE REVIEW: Hubungan Antara Riwayat Vaksin BCG dan Kejadian Kusta Pada Anak: Sebuah Tinjauan Literatur - Noer Auliyah Madani Pertiwi, Aisyah; Martini, Santi; Mohamed Gomaa Nasr, Nayla (Universitas Airlangga, 2024)
Background: Globally, 9,052 new cases of leprosy in children were reported, with a corresponding rate of 4.5 per million child population. Children are believed to be the most vulnerable group to M. leprae infections due to their immature immunity. Purpose: This study aims to determine the relationship between the history of BCG vaccination and leprosy incidence in children. Methods: This study used a literature review method that involved a systematic search. The data sources were obtained using several databases, namely Google Scholar, Proquest, Science Direct, and Pubmed. Keywords were built using the PICOS protocol and Boolean Operators, so the keywords used were